2014
DOI: 10.1016/j.physletb.2014.10.058
|View full text |Cite
|
Sign up to set email alerts
|

Shining LUX on isospin-violating dark matter beyond leading order

Abstract: Editor: W. HaxtonIsospin-violating dark matter (IVDM) has been proposed as a viable scenario to reconcile conflicting positive and null results from direct detection dark matter experiments. We show that the lowest-order dark matter-nucleus scattering rate can receive large and nucleus-dependent corrections at next-toleading order (NLO) in the chiral expansion. The size of these corrections depends on the specific couplings of dark matter to quark flavors and gluons. In general the full NLO dark-matter-nucleus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(96 citation statements)
references
References 50 publications
3
93
0
Order By: Relevance
“…In [10,11,13], the relevance of 2-body densities in DM detection has been pointed out, although as a subleading effect in the chiral counting. In this paper we find another interesting application for DM direct detection, where the two-body term plays a dominant role.…”
Section: The Role Of Proton-proton Correlationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [10,11,13], the relevance of 2-body densities in DM detection has been pointed out, although as a subleading effect in the chiral counting. In this paper we find another interesting application for DM direct detection, where the two-body term plays a dominant role.…”
Section: The Role Of Proton-proton Correlationsmentioning
confidence: 99%
“…For the experimental details of the analysis we refer the reader to [13] and references therein. The color coding is Xenon100 (red), LUX (green), CDMS-Ge (blue).…”
Section: Numerical Analysismentioning
confidence: 99%
“…As LUX experiment [11] currently imposes the most stringent bound on DM, one necessarily considers DM that has negligible interaction with the Xenon nucleus. Recent studies after the LUX result [17][18][19]27] have shown that the isospin-violating DM is still compatible with one of positive signals, those of the CDMS-II Si experiment.…”
Section: Jhep05(2014)086mentioning
confidence: 95%
“…Given the huge parameter space, it is necessary to make additional, simplifying assumptions 2 Although see [23] for important higher-order corrections to σ 0 which can reduce the value of y, albeit with large uncertainties. 3 Corrections to the single-nucleon picture underlying (2.1) in the form of two-nucleon currents can be systematically taken into account using effective field theory [29][30][31][32].…”
Section: Blind Spots and Isospin Violationmentioning
confidence: 99%